Class II malocclusion associated with mandibular deficiency and maxillary and mandibular crowding: follow-up evaluation eight years after treatment completion - Luís Antônio de Arruda Aidar
ABSTRACT This report describes the correction of a clinical case of malocclusion with anteroposterior discrepancy and transverse, sagittal and vertical deficiencies. A nonextraction technique was used to preserve space in the dental arches and control facial growth for the correction of the sagittal skeletal relationship and of overbite. The mechanics adopted efficiently corrected malocclusion: all functional and esthetic goals were achieved, and results remained stable eight years after treatment completion. This case was presented to the Committee of the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as part of the requirements necessary to obtain the BBO Diploma.